Case report: Area of focus in a case of malignant hypertension - Bosisio, Francesca Gaia; Mingardi, Desirè; Moretti, Elisabetta; Muzi, Giorgia; Russomanno, Francesco; Tassani, Nicola; Stassaldi, Deborah; Agabiti Rosei, Claudia; De Ciuceis, Carolina; Salvetti, Massimo; Muiesan, Maria Lorenza (Frontiers in Cardiovascular Medicine, 2023)
Malignant hypertension (MH) is characterized by severe hypertension (usually grade 3) associated with fundoscopic changes (flame hemorrhages and/or papilledema), microangiopathy and disseminated intravascular coagulation. In addition encephalopathy, acute heart failure and acute deterioration in renal function may be present. The term “malignant” reflects the very poor prognosis for this condition if untreated. When severe hypertension is associated with hypertension-mediated organ damage (HMOD) a life-threatening situation that requires immediate but careful intervention occurs (hypertensive emergency). In the last few years an increase in the number of patients with malignant hypertension has been observed, especially among those patients with black ethnicity. Limited access to treatment and the poor adherence to anti-hypertensive therapy may contribute to the development of hypertensive emergencies. It is considered appropriate to study patients in order to rule out thrombotic thrombocytopenic purpura and hemolytic uremic syndrome. In fact, the microvascular damage caused by malignant hypertension can favor intravascular hemolysis like Thrombotic Microangiopathies (TMs). TMs may present in three different clinical conditions: typical hemolytic uremic syndrome (HUS), atypical hemolytic uremic syndrome (aHUS) and thrombotic thrombocytopenic purpura (TTP). TMs can arise in the context of other pathological processes, including malignant hypertension.